Pentasil type zeolite and method for producing same
The pentasil-type zeolite, produced using a specific method involving a silicon source, amine, and alkaline source without fluorine, addresses the challenges of low water adsorption and high strength, achieving improved VOC selectivity and molded product strength in high humidity conditions.
Patent Information
- Application Number
- JP2023197887
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-07-19
- Filing Date
- 2023-11-22
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2039-10-18
AI Technical Summary
Existing pentasil-type zeolites face challenges in maintaining low water adsorption and high strength when used as molded products, particularly in high humidity environments, due to large primary particle sizes and difficulties in processing with fluorine sources.
A pentasil-type zeolite with a moisture adsorption amount of 4.0 g/100 g-zeolite or less at 25°C and 90% relative humidity, and primary particle sizes between 0.2 μm and 4.0 μm, is produced using a method that includes a silicon source, an amine as a structure directing agent, an alkaline source, and a crystallization step without fluorine sources, followed by treatment with an alkaline solution and calcination under water-containing vapor flow.
The resulting pentasil-type zeolite exhibits improved selectivity for VOC adsorption and enhanced strength when molded, making it suitable for applications in high humidity environments without the need for specialized equipment to handle corrosive fluorine.
Smart Images

Figure 0007647843000002 
Figure 0007647843000003 
Figure 0007647843000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a pentasil-type zeolite and a method for producing the same, and more particularly to a pentasil-type zeolite that has a low water adsorption amount, is suitable for applications requiring high hydrophobicity, such as VOC adsorbents, and has excellent strength when used as a molded product, and a method for producing the same. [Background technology]
[0002] Pentasil-type zeolites are widely used as adsorbents and catalysts. When using zeolites as VOC adsorbents, it is preferable that the zeolites do not adsorb water easily. This is because the selectivity of VOC adsorption is improved by the reduced water adsorption ability.
[0003] When zeolites are used as adsorbents or catalysts, they are generally processed into compacts and used in fixed-phase or fluidized-bed adsorption towers or reactors. If the compacts are pulverized during packing, adsorption / desorption, or catalytic reactions, this can cause equipment troubles and pressure loss, so the compacts are required to have high strength. The strength of such compacts is affected by the size of the primary particles of the raw zeolite powder.
[0004] Non-Patent Document 1 reports pentasil-type zeolite crystallized in the presence of fluorine. Pentasil-type zeolite crystallized in the presence of fluorine is less likely to adsorb water, but the primary particles are very large, 5 to 100 μm. If the primary particles are as large as 5 to 100 μm, the strength of the molded product is reduced. In addition, it is difficult to crystallize using highly corrosive fluorine using normal zeolite manufacturing equipment. [Prior art documents] [Non-patent literature]
[0005] [Non-Patent Document 1] Studies in Surface Science and Catalysis,Vol,105,p.309(1997) Summary of the Invention [Problem to be solved by the invention]
[0006] An object of the present invention is to provide a pentasil-type zeolite which is characterized by being less prone to adsorb water and having excellent strength when used as a molded product, and a method for producing the same. [Means for solving the problem]
[0007] In view of the above circumstances, the present inventors have conducted extensive research into pentasil-type zeolites and the conditions for producing the same, and as a result have discovered the pentasil-type zeolite of the present invention and a method for producing the same. That is, the present invention relates to a pentasil-type zeolite having a water adsorption amount of 4.0 g / 100 g-zeolite or less under conditions of 25° C. and a relative humidity of 90%, and a major axis diameter of primary particles of 0.2 μm or more and 4.0 μm or less, and a method for producing the same.
[0008] The pentasil-type zeolite of the present invention will now be described.
[0009] The present invention relates to a pentasil type zeolite. A pentasil type zeolite is a zeolite containing a combination of five-membered oxygen rings. The pentasil type zeolite can be at least one of MFI, MEL, and intergrowths thereof, as defined by the structure code of the International Zeolite Association (hereinafter referred to as "IZA"). Examples of MFI include ZSM-5, silicalite-1, etc., and examples of MEL include ZSM-11, silicalite-2, etc.
[0010] The crystalline phase of the pentasil-type zeolite can be identified by comparing it with at least one of the powder X-ray diffraction (hereinafter referred to as "XRD") patterns described in Collection of simulated XRD powder patterns for zeolites, Fifth revised edition, p. 483 (2007) or the XRD patterns described in The Pentasil Family in Disorder in Zeolite Frameworks on the IZA Structural Committee homepage (http: / / www.iza-struture.org / databases / ).
[0011] The pentasil type zeolite of the present invention has a water adsorption amount of 4.0 g / 100 g-zeolite or less under conditions of 25° C. and 90% relative humidity. If the water adsorption amount is more than 4.0 g / 100 g-zeolite under conditions of 25° C. and 90% relative humidity, the selectivity of VOC adsorption decreases and is unsuitable. Even in a high humidity environment of 90% relative humidity, the zeolite is less likely to adsorb water even when used as a VOC adsorbent in a high humidity season or in a high humidity area, so that the selectivity of VOC adsorption is improved when the pentasil type zeolite of the present invention is used as a VOC adsorbent. The smaller the water adsorption amount under conditions of 25° C. and 90% relative humidity, the more preferable. The water adsorption amount under conditions of 25° C. and 90% relative humidity is preferably 3.5 g / 100 g-zeolite or less, more preferably 3.0 g / 100 g-zeolite or less, and even more preferably 2.5 g / 100 g-zeolite or less.
[0012] The pentasil type zeolite of the present invention has a major axis diameter of the primary particles of 0.2 μm or more and 4.0 μm or less. If the major axis diameter of the primary particles is less than 0.2 μm, it is inappropriate because filtration and washing are difficult, and if it exceeds 4.0 μm, it is inappropriate because the strength of the molded body is low and the surface area is small. The major axis diameter of the primary particles is preferably 0.2 μm or more and 3.5 μm or less, more preferably 0.2 μm or more and 3.0 μm or less, even more preferably 0.2 μm or more and 2.5 μm or less, particularly preferably 0.4 μm or more and 2.5 μm or less, 0.4 μm or more and 2.0 μm or less, 0.6 μm or more and 2.0 μm or less, or 0.6 μm or more and 1.5 μm or less.
[0013] The major axis diameter of the primary particles of the pentasil-type zeolite of the present invention is measured using an electron microscope. Any electron microscope capable of obtaining particle images required for measurement may be used, and typically includes a scanning electron microscope (hereinafter, referred to as "SEM"). The method for measuring the major axis diameter of the primary particles is as described in <Morphological Observation of Primary Particles> in the Examples.
[0014] The relationship between the major axis diameter (particle diameter) of primary particles and the strength of a green body is expressed by the following Rumpf equation.
[0015] σ = 1.1 × (1-ε) × F ad / (ε×D p 2 ) σ: force required for fracture, ε: porosity, F ad : Interparticle force, D p : Particle size As is obvious from the Rumpf formula, D p When becomes smaller, σ becomes larger, that is, the smaller the particle size, the higher the strength of the molded body.
[0016] The aspect ratio of the primary particles of the pentasil-type zeolite of the present invention is preferably 1.0 or more and 3.0 or less. It is self-evident from the definition that the aspect ratio of the primary particles is not less than 1.0. The smaller the aspect ratio of the primary particles, the more preferable it is, as the particle packing property is higher, and as a result, the strength of the molded body is higher. The effect of particle shape on particle packing property is disclosed in the document "Powder Bed Operation and Simulation, compiled by the Society of Powder Technology", page 20, line 1 to page 22, line 5. Regarding the effect of particle shape on particle packing property, spherical particles or particles with a small aspect ratio that are slightly distorted from a spherical shape have a higher particle packing property than non-spherical particles with a large aspect ratio such as crushed particles. That is, in the present invention, the smaller the aspect ratio of the primary particles, the more preferable it is. The aspect ratio of the primary particles is more preferably 1.0 or more and 2.5 or less, even more preferably 1.0 or more and 2.3 or less, and particularly preferably 1.0 or more and 2.1 or less, 1.0 or more and 1.9 or less, 1.0 or more and 1.7 or less, 1.0 or more and 1.5 or less, or 1.0 or more and 1.4 or less.
[0017] The primary particles of the pentasil-type zeolite of the present invention have an angular shape. Here, the term "angular" refers to primary particles having sharp corners when observed by morphological observation of the primary particles using an electron microscope, and examples of such shapes include rectangular parallelepiped, nearly rectangular parallelepiped, cubic, and nearly cubic. On the other hand, primary particles having a spherical, nearly spherical, or elliptical shape are not clearly visible when observed by morphological observation of the primary particles using an electron microscope. , it is rounded and has no sharp corners, which is different from the present invention.
[0018] The pentasil-type zeolite of the present invention preferably has a SiO2 / Al2O3 (molar ratio, the same applies below) of 200 or more. The higher the SiO2 / Al2O3, the more hydrophobic the zeolite is, and the less likely it is that the zeolite will adsorb water. Therefore, when the pentasil-type zeolite of the present invention is used as a VOC adsorbent or the like, the selectivity of VOC adsorption is improved. The SiO2 / Al2O3 is more preferably 400 or more, even more preferably 800 or more, and particularly preferably 1500 or more.
[0019] The pentasil-type zeolite of the present invention has a BET specific surface area of 300 m 2 / g or more. The higher the BET specific surface area, the more preferable it is, since the amount of adsorption increases when used as an adsorbent, and the activity and life of the catalyst improve when used as a catalyst. The BET specific surface area is more preferably 330 m 2 / g or more, more preferably 350m 2 / g or more.
[0020] When the pentasil-type zeolite of the present invention is used as an adsorbent or catalyst, the content of Na2O is preferably 1.00 weight percent or less, since sodium corrosion of equipment, piping, etc. is more unlikely to occur. The content of Na2O is more preferably 0.80 weight percent or less, even more preferably 0.60 weight percent or less, and particularly preferably 0.40 weight percent or less. The content of Na2O may be 0.05 weight percent or more, or 0.10 weight percent or more.
[0021] The pentasil type zeolite of the present invention can be used as an adsorbent or catalyst. In particular, the pentasil type zeolite of the present invention is suitable for use as a VOC adsorbent. When using zeolite as a VOC adsorbent, it is preferable that the zeolite does not easily adsorb water. This is because the selectivity of VOC adsorption is improved by being less likely to adsorb water. Since the pentasil type zeolite of the present invention does not easily adsorb water, it is particularly suitable for use as a VOC adsorbent. In addition, when used as an adsorbent or catalyst, zeolite is generally processed into a molded body and used in a fixed phase or fluidized bed adsorption tower or reactor. If the molded body is powdered during filling, adsorption / desorption, or catalytic reaction, it can cause equipment troubles and pressure loss, so the molded body is required to have high strength. The pentasil type zeolite of the present invention has excellent strength, such as abrasion resistance strength and crushing strength, when processed into a molded body.
[0022] Next, the method for producing the pentasil-type zeolite of the present invention will be described.
[0023] The pentasil-type zeolite of the present invention can be produced by a production method including a crystallization step of crystallizing a mixture containing a silicon source, an amine as a structure directing agent, and an alkali source, but not containing a fluorine source, a step of contacting the zeolite with an alkali solution having a pH of 10 to 14, and a step of calcining at a temperature of 500 to 1000°C under a flow of water-containing steam.
[0024] The mixture used in the crystallization process comprises a silicon source, an amine as a structure directing agent, and an alkali source.
[0025] The silicon source is a compound containing silicon (Si), and examples thereof include at least one of the group consisting of tetraethoxysilane, silica sol, fumed silica, precipitated silica, sodium silicate, and amorphous silicic acid. Since it is suitable for industrial production, the silicon source is preferably at least one of the group consisting of silica sol, fumed silica, precipitated silica, sodium silicate, and amorphous silicic acid.
[0026] The structure directing agent for pentasil-type zeolite is disclosed in the document "Zeolites, Vol. 3, p. 282 (1983)", and includes amines such as normal propylamine, dinormal propylamine, tripropylamine, dinormal butylamine, dipropylenetriamine, dihexamethylenetriamine, triethylenetetramine, diethylenetriamine, ethanolamine, and propanolamine, quaternary ammonium cations such as tetrapropylammonium and tetraethylammonium, and others such as glycerol, alcohols, and morpholine. In the present invention, among these structure directing agents, amines are used. By using amines, the water adsorption amount at a relative humidity of 90% is easily reduced by going through a step of contacting with an alkaline solution of pH 10 to 14 and a step of calcining under a water-containing steam flow, and when a structure directing agent other than amines is used, the water adsorption amount at a relative humidity of 90% is not easily reduced even after going through a step of contacting with an alkaline solution of pH 10 to 14 and a step of calcining under a water-containing steam flow. Among the amines, normal propylamine, di-normal propylamine, and tripropylamine are preferred because the amount of water adsorption at a relative humidity of 90% is likely to be reduced by going through a step of contacting with an alkaline solution having a pH of 10 to 14 and a step of calcining under a flow of water-containing steam.
[0027] In order to fully utilize the effect of the structure directing agent, the molar ratio of the structure directing agent to silica in the mixture (hereinafter referred to as "structure directing agent / SiO2") is preferably 0.04 or more and 0.5 or less. This is economical because it prevents the coexistence of amorphous structures other than the pentasil structure and reduces the amount of expensive raw materials used. It is even more preferable that it is 0.08 or more and 0.3 or less.
[0028] The alkali source is the hydroxide anion (OH -) and examples thereof include at least one member selected from the group consisting of hydroxides containing an alkali metal or tetraalkylammonium hydroxide. When the alkali source is a hydroxide containing an alkali metal, examples thereof include at least one member selected from the group consisting of lithium hydroxide, sodium hydroxide, potassium hydroxide, rubidium hydroxide, and cesium hydroxide. When the alkali source is a tetraalkylammonium hydroxide, examples thereof include at least one member selected from the group consisting of tetraethylammonium hydroxide, tetrapropylammonium hydroxide, and tetrabutylammonium hydroxide.
[0029] Hydroxide anion (OH - ) acts as a mineralizer. To obtain its full effect as a mineralizer, OH is required for the silica in the mixture. - The molar ratio of OH - / SiO2) is preferably 0.08 or more and 0.2 or less, and more preferably 0.09 or more and 0.18 or less.
[0030] The mixture preferably has at least the following molar composition:
[0031] Structure directing agent / SiO2 0.04 or more, 0.5 or less OH - / SiO20.08 or more, 0.2 or less The ratios in the above compositions are molar ratios.
[0032] More preferred compositions include the following:
[0033] Structure directing agent / SiO2 0.08 or more, 0.3 or less OH - / SiO20.09 or more, 0.18 or less Additionally, the mixture used in the crystallization step does not contain a fluorine source.
[0034] The fluorine source refers to a compound raw material of hydrofluoric acid, ammonium fluoride, sodium fluoride, potassium fluoride, cesium fluoride, hydrosilicic acid, ammonium silicic fluoride, sodium silicic fluoride, potassium silicic fluoride, and cesium silicic fluoride. By not including a fluorine source in the mixture, the primary particles do not become large, 5 to 100 μm, as in Non-Patent Documents 1 and 2, and the major axis diameter of the primary particles becomes 4.0 μm or less. In addition, when the mixture contains fluorine, it is necessary to use a corrosion-resistant material for the production equipment, but since the production method of the present invention does not use fluorine, normal zeolite production equipment can be used for crystallization.
[0035] It is preferable that the mixture does not contain fluorine, that is, the fluorine content is 0 ppm by weight. However, taking into consideration the measurement error due to normal composition analysis, the fluorine content of the mixture is below the detection limit, and may be 100 ppm by weight or less, or even 10 ppm by weight or less. Since the mixture does not contain fluorine or fluorine compounds, it can be produced using general-purpose equipment. The fluorine content of the mixture can be measured by a general measurement method such as XRF.
[0036] The mixture of the above composition is crystallized in a sealed pressure vessel at a temperature of 80 to 200° C. for a sufficient period of time to obtain a pentasil-type zeolite.
[0037] The crystallization temperature is not particularly limited, but the lower the crystallization temperature, the larger the BET specific surface area of the resulting pentasil-type zeolite. Therefore, the crystallization temperature is preferably 160°C or less, more preferably 150°C or less, even more preferably 140°C or less, and particularly preferably 130°C or less.
[0038] In the step of contacting zeolite with an alkaline solution having a pH of 10 to 14, the hydrophilic amorphous parts present in small amounts in the zeolite are removed. By removing the hydrophilic amorphous parts, the zeolite becomes less likely to adsorb water.
[0039] The pH range of the alkaline solution is 10 to 14. If the pH is less than 10, the removal of the hydrophilic amorphous portion does not proceed sufficiently, and if the pH is more than 14, the zeolite dissolves. The pH of the alkaline solution is preferably 11 to 13.5. The alkaline solution is a hydrated solution containing hydroxide anions (OH - ) is an aqueous solution of a compound containing the above-mentioned alkali metal, and examples thereof include at least one of the group consisting of hydroxides containing an alkali metal or tetraalkylammonium hydroxide. When the alkali source is a hydroxide containing an alkali metal, examples thereof include at least one of the group consisting of lithium hydroxide, sodium hydroxide, potassium hydroxide, rubidium hydroxide, and cesium hydroxide. When the alkali source is a tetraalkylammonium hydroxide, examples thereof include at least one of the group consisting of tetraethylammonium hydroxide, tetrapropylammonium hydroxide, and tetrabutylammonium hydroxide. The temperature in the step of contacting with the alkali solution is not particularly limited, but in order to sufficiently remove the hydrophilic amorphous portion, the temperature is preferably 20 to 90°C, and more preferably 40 to 80°C. The contact time is not particularly limited, but in order to sufficiently remove the hydrophilic amorphous portion, the temperature is preferably 0.2 to 10 hours, and more preferably 0.5 to 8 hours.
[0040] In the process of calcining at a temperature of 500 to 1000°C under the flow of water-containing steam, the silanol in the zeolite undergoes dehydration condensation, so that the zeolite is less likely to adsorb water. The temperature range is 500 to 1000°C. If the temperature is lower than 500°C, the dehydration condensation of silanol does not proceed easily, and if the temperature is higher than 1000°C, the zeolite structure collapses. The calcination temperature is preferably 600 to 1000°C, more preferably 600 to 900°C. The flow of water-containing steam means an atmosphere containing water vapor, and is not particularly limited as long as it contains water vapor, such as air containing water vapor, nitrogen containing water vapor, an inert atmosphere such as argon, etc. The calcination time is not particularly limited, but is preferably 0.5 to 10 hours, more preferably 1 to 8 hours.
[0041] The production method of the present invention may include, after the crystallization step, one or more of a washing step, a drying step, and a structure-directing agent removal step.
[0042] In the washing step, the pentasil-type zeolite obtained in the crystallization step is separated into solid and liquid to obtain the solid phase. The washing method is arbitrary, and the crystallized product may be washed with pure water.
[0043] If alkali metals remain in the pentasil-type zeolite after the washing step, it may be washed again. This allows the remaining alkali metals to be reduced or removed. An example of reducing the alkali metals is to adjust the sodium content to 1.00 weight percent or less in terms of Na2O. An example of a method for washing again is mixing the washed pentasil-type zeolite with at least one selected from the group consisting of water, an aqueous ammonium chloride solution, dilute hydrochloric acid, dilute sulfuric acid, and dilute nitric acid. The mixed pentasil-type zeolite may be washed by any method, such as washing with pure water.
[0044] In the drying step, the pentasil-type zeolite is dried, for example, by treating it in the air at 100 to 200°C.
[0045] In the structure-directing agent removal step, the structure-directing agent is removed. In the crystallization step, the pentasil-type zeolite is obtained in a state in which the structure-directing agent is contained. The structure-directing agent can be appropriately removed from the pentasil-type zeolite containing such a structure-directing agent. Examples of a method for removing the structure-directing agent include calcination, decomposition, washing, and the like. When the structure-directing agent is removed by calcination, it can be treated under a flow of oxygen-containing gas at 300 to 800°C, or further 400 to 700°C, for 0.5 to 12 hours.
[0046] The production method of the present invention may include one or more of a washing step and a drying step after the step of contacting zeolite with an alkaline solution having a pH of 10 to 14.
[0047] In the washing step, the pentasil-type zeolite obtained in the step of contacting the zeolite with an alkaline solution having a pH of 10 to 14 is separated into solid and liquid to obtain the solid phase. Any washing method may be used, and the crystallized product may be washed with pure water.
[0048] If alkali metals remain in the pentasil-type zeolite after the washing step, it may be washed again. This allows the remaining alkali metals to be reduced or removed. An example of reducing the alkali metals is to adjust the sodium content to 1.00 weight percent or less in terms of Na2O. An example of a method for washing again is mixing the washed pentasil-type zeolite with at least one selected from the group consisting of water, an aqueous ammonium chloride solution, dilute hydrochloric acid, dilute sulfuric acid, and dilute nitric acid. The mixed pentasil-type zeolite may be washed by any method, such as washing with pure water.
[0049] In the drying step, the pentasil-type zeolite is dried, for example, by treating it in the air at 100 to 200°C. Effect of the Invention
[0050] The present invention provides a pentasil-type zeolite which is less susceptible to water adsorption than conventional zeolites and has excellent strength when used as a molded product, and a method for producing the pentasil-type zeolite. [Brief description of the drawings]
[0051] [Figure 1] FIG. 2 is a schematic diagram showing a method for measuring the major axis diameter of a primary particle diameter. [Diagram 2] 1 is an SEM image of the pentasil-type zeolite of Example 1. [Diagram 3] 1 is an SEM observation image of MFI type zeolite (product name: HSZ (registered trademark)-840HOA, manufactured by Tosoh Corporation). [Figure 4] 1 is an SEM observation image of MFI type zeolite (product name: HSZ (registered trademark)-890HOA, manufactured by Tosoh Corporation). [Diagram 5]1 is an SEM image of the pentasil-type zeolite of Comparative Example 6. EXAMPLES
[0052] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples.
[0053] The measurement methods used in the examples and comparative examples are as follows.
[0054] <Crystal structure identification> The XRD measurement of the sample was carried out using an XRD device (product name: Ultima IV, manufactured by Rigaku). The radiation source used was CuKα radiation (λ = 1.5405 Å), and the measurement range was 2θ = 5° to 40°.
[0055] The samples were identified by comparing the obtained XRD patterns with those described in Collection of simulated XRD powder patterns for zeolites, Fifth revised edition, p. 483 (2007).
[0056] <Morphological observation of primary particles> The morphology of the primary particles was observed using an electron microscope (instrument name: JSM-6390LV, manufactured by JEOL).
[0057] The major axis diameter of the primary particles is a value measured based on the definition described in the 5th item, 3rd line to the 6th item, 2nd line of the document "Particle Size Measurement Technology, edited by the Powder Technology Society". Hereinafter, it will be explained with reference to the schematic diagram (Figure 1) showing the measurement method of the major axis diameter. One primary particle 1 placed statically on a plane is observed from a direction perpendicular to the plane. For the contour 2 of the projection image of the primary particle 1, among the lengths when it is sandwiched by two parallel lines 3 in contact with it, the minimum length is defined as the minor axis diameter 5 of the primary particle, and the length measured in a direction perpendicular to the minor axis diameter of the primary particle is defined as the major axis diameter 4 of the primary particle. The major axis diameter of the primary particle was obtained by randomly extracting 30 primary particles and calculating the average of the measured values of the major axis diameters of individual primary particles. The aspect ratio of the primary particle is obtained by dividing the major axis diameter of the primary particle by the minor axis diameter, and was obtained by randomly extracting 30 primary particles and calculating the average of the aspect ratios of individual primary particles.
[0058] <Composition Analysis> Composition analysis was performed using a fluorescence X-ray apparatus (trade name: RIX2100, manufactured by Rigaku). As a pretreatment, the product was calcined at 600 °C for 1 hour. From the obtained analysis results, the SiO2 / Al2O3 ratio and the Na2O content of the product were determined.
[0059] <BET Specific Surface Area> The BET specific surface area of the sample was determined by measurement according to JIS 8830. A general specific surface area measurement apparatus (trade name: BELSORP-miniII, manufactured by MicrotracBEL) was used for the measurement. As a pretreatment, the sample was held at 350 °C for 2 hours. The BET specific surface area of the sample after pretreatment was measured.
[0060] <Water Adsorption Amount> The measurement of the water adsorption amount was carried out using a vapor adsorption measurement apparatus (trade name: BELSORP-max, manufactured by MicrotracBEL). The measurement was performed at 25 °C. As a pretreatment, the sample was held at 350 °C for 2 hours. The water adsorption amount of the sample after pretreatment was measured, and the water adsorption amount per 100 g of zeolite (hereinafter referred to as "g / 100g-zeolite") at a relative humidity of 90% was measured.
[0061] Example 1 Granular amorphous silicic acid was obtained by mixing an aqueous solution of sodium silicate and sulfuric acid. The obtained granular amorphous silicic acid, normal propylamine (hereinafter referred to as "NPA"), sodium hydroxide, and pure water were mixed to obtain a mixture having the following molar composition.
[0062] SiO2 / Al2O3= 3800 NPA / SiO2= 0.25 OH / SiO2= 0.12 Na / SiO2= 0.12 H2O / SiO2= 10 To the above mixture, MFI type zeolite was added as seed crystals to obtain a raw material mixture. The amount of seed crystals added was 0.5% by weight based on the weight of SiO2 and Al2O3 in the above mixture. The obtained raw material mixture was filled into a stainless steel reaction vessel and sealed. The reaction vessel was then heated to 115°C while rotating at 55 rpm. After heating, the reaction vessel was held at 115°C for 36 hours while rotating, thereby crystallizing the mixture and obtaining a crystallized slurry.
[0063] The crystallized slurry was cooled, filtered, washed with pure water, added to a 1.2 N HCl aqueous solution, mixed, and washed with pure water to ion-exchange the sodium in the pentasil zeolite with protons, and then dried at 110°C to obtain pentasil zeolite.
[0064] The obtained pentasil-type zeolite was heat-treated in a sodium hydroxide aqueous solution of pH 13 at 75°C for 2.5 hours, then washed with pure water, added to a 1.2 N HCl aqueous solution, mixed, and washed with pure water to ion-exchange the sodium in the pentasil-type zeolite with protons, and then dried at 110°C and calcined at 720°C for 2 hours under a stream of water-containing steam to obtain pentasil-type zeolite.
[0065] The XRD pattern of the product matched that of the MFI structure, and it was confirmed to be a pentasil-type zeolite.
[0066] The water adsorption amount of the zeolite at 25° C. and a relative humidity of 90% was 2.3 g / 100 g of zeolite.
[0067] The SEM image of the zeolite is shown in Figure 2. The major axis diameter of the primary particles measured from the SEM image was 1.0 μm, and the aspect ratio of the primary particles was 2.0. The shape of the primary particles was angular (approximately rectangular parallelepiped).
[0068] The zeolite has a SiO2 / Al2O3 (molar ratio) of 1900 and a BET specific surface area of 373 m 2 / g, and the Na2O content was less than 0.01 weight percent.
[0069] Example 2 A pentasil-type zeolite was obtained in the same manner as in Example 1, except that the calcination temperature was 850°C.
[0070] The XRD pattern of the product matched that of the MFI structure, and it was confirmed to be a pentasil-type zeolite.
[0071] The amount of water adsorption of the zeolite at 25°C and 90% relative humidity was 1.1 g / 100 g-zeolite. The major axis diameter of the primary particles measured from the SEM observation image was 1.0 μm, and the aspect ratio of the primary particles was 2.0. The shape of the primary particles was angular (approximately rectangular parallelepiped).
[0072] The zeolite has a SiO2 / Al2O3 (molar ratio) of 1900 and a BET specific surface area of 372 m 2 / g, and the Na2O content was less than 0.01 weight percent.
[0073] Example 3 A pentasil-type zeolite was obtained in the same manner as in Example 1, except that the calcination temperature was 650°C.
[0074] The XRD pattern of the product matched that of the MFI structure, and it was confirmed to be a pentasil-type zeolite.
[0075] The amount of water adsorption of the zeolite at 25°C and 90% relative humidity was 2.8 g / 100 g of zeolite. The major axis diameter of the primary particles measured from the SEM observation image was 1.0 μm, and the aspect ratio of the primary particles was 2.0. The shape of the primary particles was angular (approximately rectangular parallelepiped).
[0076] The zeolite has a SiO2 / Al2O3 (molar ratio) of 1900 and a BET specific surface area of 386 m 2 / g, and the Na2O content was less than 0.01 weight percent.
[0077] Example 4 In the same manner as in Example 1, the product was crystallized, filtered, washed with pure water, added to a 1.2 N HCl aqueous solution, mixed, and washed with pure water to ion-exchange the sodium in the pentasil-type zeolite with protons, and then dried at 110° C. to obtain pentasil-type zeolite.
[0078] The obtained pentasil-type zeolite was heat-treated in a sodium hydroxide aqueous solution of pH 13 at 60°C for 1 hour, then washed with pure water, added to a 1.2 N HCl aqueous solution, mixed, and washed with pure water to ion-exchange the sodium in the pentasil-type zeolite with protons, and then dried at 110°C and calcined for 2 hours at 780°C under a stream of water-containing steam to obtain pentasil-type zeolite.
[0079] The XRD pattern of the product matched that of the MFI structure, and it was confirmed to be a pentasil-type zeolite.
[0080] The amount of water adsorption of the zeolite at 25°C and 90% relative humidity was 3.8 g / 100 g of zeolite. The major axis diameter of the primary particles measured from the SEM observation image was 1.0 μm, and the aspect ratio of the primary particles was 2.0. The shape of the primary particles was angular (approximately rectangular parallelepiped).
[0081] The zeolite has a SiO2 / Al2O3 (molar ratio) of 1900 and a BET specific surface area of 400m 2 / g, and the Na2O content was less than 0.01 weight percent.
[0082] Example 5 Pentasil-type zeolite was obtained in the same manner as in Example 1, except that the molar composition of the mixture was OH / SiO2 = 0.20, Na / SiO2 = 0.20, the mixture was added to a 1.2 N HCl aqueous solution after heat treatment, mixed, and washed with pure water, so that 0.05 weight percent Na2O remained when the sodium in the pentasil-type zeolite was ion-exchanged with protons, and the firing temperature was 680°C.
[0083] The XRD pattern of the product matched that of the MFI structure, and it was confirmed to be a pentasil-type zeolite.
[0084] The amount of water adsorption of the zeolite at 25°C and 90% relative humidity was 2.1 g / 100 g of zeolite. The major axis diameter of the primary particles measured from the SEM observation image was 0.8 μm, and the aspect ratio of the primary particles was 1.3. The shape of the primary particles was also angular (approximately cubic).
[0085] The SiO2 / Al2O3 (molar ratio) of the zeolite is 1210, and the BET specific surface area is 372 m 2 / g, and the Na2O content was 0.05 weight percent.
[0086] Example 6 Pentasil-type zeolite was obtained in the same manner as in Example 1, except that the molar composition of the mixture was OH / SiO2 = 0.19, Na / SiO2 = 0.19, the mixture was added to a 1.2 N HCl aqueous solution after heat treatment, mixed, and washed with pure water, so that 0.13 weight percent Na2O remained when the sodium in the pentasil-type zeolite was ion-exchanged with protons, and the firing temperature was 600°C.
[0087] The XRD pattern of the product matched that of the MFI structure, and it was confirmed to be a pentasil-type zeolite.
[0088] The amount of water adsorption of the zeolite at 25°C and 90% relative humidity was 2.5g / 100g-zeolite. The major axis diameter of the primary particles measured from the SEM observation image was 0.8μm, and the aspect ratio of the primary particles was 1.3. The shape of the primary particles was angular (approximately cubic).
[0089] The SiO2 / Al2O3 (molar ratio) of the zeolite is 1690, and the BET specific surface area is 368 m 2 / g, and the Na2O content was 0.13 weight percent.
[0090] Example 7 A pentasil-type zeolite was obtained in the same manner as in Example 1, except that the molar composition of the mixture was OH / SiO2=0.15 and Na / SiO2=0.15.
[0091] The XRD pattern of the product matched that of the MFI structure, and it was confirmed to be a pentasil-type zeolite.
[0092] The amount of water adsorption of the zeolite at 25°C and 90% relative humidity was 2.2 g / 100 g of zeolite. The major axis diameter of the primary particles measured from the SEM observation image was 0.9 μm, and the aspect ratio of the primary particles was 1.5. The shape of the primary particles was angular (approximately cubic).
[0093] The SiO2 / Al2O3 (molar ratio) of the zeolite is 1560, and the BET specific surface area is 370m 2 / g, and the Na2O content was less than 0.01 weight percent.
[0094] Example 8 A pentasil-type zeolite was obtained in the same manner as in Example 7, except that the amount of seed crystals added was 0.05% by weight.
[0095] The XRD pattern of the product matched that of the MFI structure, and it was confirmed to be a pentasil-type zeolite.
[0096] The amount of water adsorption of the zeolite at 25°C and 90% relative humidity was 2.1 g / 100 g of zeolite. The major axis diameter of the primary particles measured from the SEM observation image was 2.2 μm, and the aspect ratio of the primary particles was 1.8. The shape of the primary particles was angular (approximately rectangular parallelepiped).
[0097] The SiO2 / Al2O3 (molar ratio) of the zeolite is 1600, and the BET specific surface area is 365m 2 / g, and the Na2O content was less than 0.01 weight percent.
[0098] Example 9 Pentasil-type zeolite was obtained in the same manner as in Example 1, except that the molar composition of the mixture was OH / SiO2 = 0.20, Na / SiO2 = 0.20, the amount of seed crystals added was 3.0 wt%, the crystallization temperature was 105°C, and the crystallization time was 72 hours.
[0099] The XRD pattern of the product matched that of the MFI structure, and it was confirmed to be a pentasil-type zeolite.
[0100] The amount of water adsorption of the zeolite at 25°C and 90% relative humidity was 2.4 g / 100 g of zeolite. The major axis diameter of the primary particles measured from the SEM observation image was 0.4 μm, and the aspect ratio of the primary particles was 1.2. The shape of the primary particles was angular (approximately cubic).
[0101] The zeolite has a SiO2 / Al2O3 (molar ratio) of 1100 and a BET specific surface area of 385 m 2 / g, and the Na2O content was less than 0.01 weight percent.
[0102] Comparative Example 1 The amount of moisture adsorption of MFI zeolite (product name: HSZ (registered trademark)-840HOA, manufactured by Tosoh Corporation) was measured, and the major axis diameter of the primary particles was measured by SEM observation. The amount of moisture adsorption under conditions of 25°C and relative humidity of 90% was 11.6 g / 100 g of zeolite. The SEM observation image is shown in Figure 3. The major axis diameter of the primary particles was 4.0 μm, and the aspect ratio of the primary particles was 1.9. The shape of the primary particles was also angular (approximately rectangular parallelepiped).
[0103] The SiO2 / Al2O3 molar ratio of the zeolite is 38, and the BET specific surface area is 330m 2 / g, and the Na2O content was less than 0.01 weight percent.
[0104] Comparative Example 2 The amount of moisture adsorption of MFI zeolite (product name: HSZ (registered trademark)-890HOA, manufactured by Tosoh Corporation) was measured, and the major axis diameter of the primary particles was measured by SEM observation. The amount of moisture adsorption under conditions of 25°C and relative humidity of 90% was 6.6 g / 100 g of zeolite. The SEM observation image is shown in Figure 4. The major axis diameter of the primary particles was 6.1 μm, and the aspect ratio of the primary particles was 4.0. The shape of the primary particles was also angular (approximately rectangular parallelepiped).
[0105] The SiO2 / Al2O3 molar ratio of the zeolite is 1900, and the BET specific surface area is 300m 2 / g, and the Na2O content was less than 0.01 weight percent.
[0106] Comparative Example 3 In the same manner as in Example 1, the product was crystallized, filtered, washed with pure water, added to a 1.2 N HCl aqueous solution, mixed, and washed with pure water to ion-exchange the sodium in the pentasil-type zeolite with protons, and then dried at 110°C to obtain pentasil-type zeolite (the step of contacting with an alkaline solution of pH 10 to 14 and the step of calcining under a water-containing steam flow were not performed).
[0107] The XRD pattern of the product matched that of the MFI structure, and it was confirmed to be a pentasil-type zeolite.
[0108] The amount of water adsorption of the zeolite at 25°C and 90% relative humidity was 8.1 g / 100 g of zeolite. The major axis diameter of the primary particles measured from the SEM observation image was 1.0 μm, and the aspect ratio of the primary particles was 2.0. The shape of the primary particles was angular (approximately rectangular parallelepiped).
[0109] The zeolite has a SiO2 / Al2O3 (molar ratio) of 1900 and a BET specific surface area of 379 m 2 / g, and the Na2O content was less than 0.01 weight percent.
[0110] Comparative Example 4 In the same manner as in Example 1, the product was crystallized, filtered, washed with pure water, added to a 1.2 N HCl aqueous solution, mixed, and washed with pure water to ion-exchange the sodium in the pentasil-type zeolite with protons, and then dried at 110° C. to obtain pentasil-type zeolite.
[0111] The obtained pentasil-type zeolite was heat-treated in a sodium hydroxide aqueous solution of pH 13 at 75°C for 2.5 hours, then washed with pure water, added to a 1.2 N HCl aqueous solution, mixed, and washed with pure water to ion-exchange the sodium in the pentasil-type zeolite with protons, and then dried at 110°C to obtain pentasil-type zeolite (a step of calcining under a stream of water-containing steam was not performed).
[0112] The XRD pattern of the product matched that of the MFI structure, and it was confirmed to be a pentasil-type zeolite.
[0113] The amount of water adsorption of the zeolite at 25°C and 90% relative humidity was 4.4 g / 100 g of zeolite. The major axis diameter of the primary particles measured from the SEM observation image was 1.0 μm, and the aspect ratio of the primary particles was 2.0. The shape of the primary particles was angular (approximately rectangular parallelepiped).
[0114] The zeolite has a SiO2 / Al2O3 (molar ratio) of 1900 and a BET specific surface area of 411 m2 / g, and the Na2O content was less than 0.01 weight percent.
[0115] Comparative Example 5 In the same manner as in Example 1, the product was crystallized, filtered, washed with pure water, added to a 1.2 N HCl aqueous solution, mixed, and washed with pure water to ion-exchange the sodium in the pentasil-type zeolite with protons. Thereafter, the product was dried at 110°C and calcined at 720°C for 2 hours under a stream of water-containing steam to obtain a pentasil-type zeolite (a step of contacting the product with an alkaline solution of pH 10 to 14 was not performed).
[0116] The XRD pattern of the product matched that of the MFI structure, and it was confirmed to be a pentasil-type zeolite.
[0117] The amount of water adsorption of the zeolite at 25°C and 90% relative humidity was 6.2 g / 100 g of zeolite. The major axis diameter of the primary particles measured from the SEM observation image was 1.0 μm, and the aspect ratio of the primary particles was 2.0. The shape of the primary particles was angular (approximately rectangular parallelepiped).
[0118] The zeolite has a SiO2 / Al2O3 (molar ratio) of 1900 and a BET specific surface area of 410 m 2 / g, and the Na2O content was less than 0.01 weight percent.
[0119] Comparative Example 6 The sodium silicate aqueous solution and sulfuric acid were mixed to obtain granular amorphous silicic acid. The obtained granular amorphous silicic acid, tetrapropylammonium bromide aqueous solution, sodium hydroxide, and pure water were mixed to obtain a mixture having the following molar composition (TPA + indicates the tetrapropylammonium cation.
[0120] SiO2 / Al2O3= 3800 TPA + / SiO2= 0.05 OH / SiO2= 0.17 Na / SiO2= 0.17 H2O / SiO2= 10 Crystallization was carried out in the same manner as in Example 1, except that the above mixture was used and the crystallization temperature was 135° C., to obtain a crystallized slurry.
[0121] The crystallized slurry was cooled, filtered, washed, and dried at 110°C. It was then calcined in air at 580°C. It was then added to a 1N HCl aqueous solution, mixed, and washed with pure water to exchange the sodium in the pentasil zeolite for protons. The resulting mixture was then dried at 110°C to obtain pentasil zeolite.
[0122] The obtained pentasil-type zeolite was heat-treated in a sodium hydroxide aqueous solution of pH 13 at 60°C for 1 hour, then washed with pure water, added to a 1.2 N HCl aqueous solution, mixed, and washed with pure water to ion-exchange the sodium in the pentasil-type zeolite with protons, and then dried at 110°C and calcined at 780°C for 2 hours under a stream of water-containing steam to obtain pentasil-type zeolite.
[0123] The XRD pattern of the product matched that of the MFI structure, and it was confirmed to be a pentasil-type zeolite.
[0124] The water adsorption amount of the zeolite at 25° C. and a relative humidity of 90% was 6.2 g / 100 g of zeolite.
[0125] The SEM image of the zeolite is shown in Figure 5. The major axis diameter of the primary particles measured from the SEM image was 0.83 μm, and the aspect ratio of the primary particles was 1.3. The shape of the primary particles was also approximately spherical.
[0126] The zeolite has a SiO2 / Al2O3 (molar ratio) of 1900 and a BET specific surface area of 406 m 2 / g, and the Na2O content was less than 0.01 weight percent.
[0127] <Toluene adsorption amount> The pentasil-type zeolites obtained in Examples 1 and 5 and Comparative Examples 2 and 3 were used to evaluate the adsorption amount of toluene, which is one of the representative components of VOCs.
[0128] The amount of toluene adsorption was measured using a vapor adsorption measuring device (product name: BELSORP-maxII, manufactured by Microtrack Bell). The measurement was performed at 25°C. As a pretreatment, the sample was kept at 350°C for 2 hours. The amount of toluene adsorption was measured for the pretreated sample, and the amount of toluene adsorption per 100 g of zeolite at an equilibrium pressure of 0.01 kPa (hereinafter referred to as "g / 100 g-zeolite") was measured. In addition, the toluene / water adsorption selectivity was calculated by the amount of toluene adsorption per 100 g of zeolite at an equilibrium pressure of 0.01 kPa / the amount of water adsorption per 100 g of zeolite at a relative humidity of 90%. The results are shown in Table 1.
[0129] [Table 1]
[0130] As is clear from Table 1, the pentasil-type zeolites of the examples had a high toluene / water adsorption selectivity ratio. It can be said that the pentasil-type zeolites of the present invention are suitable as VOC adsorbents. [Industrial Applicability]
[0131] The pentasil-type zeolite of the present invention can be used as an adsorbent or a catalyst. In particular, it is suitable as an adsorbent for VOCs, and as a catalyst for petrochemical and petroleum refining. [Explanation of symbols]
[0132] 1 A primary particle placed on a flat surface 2. The contour of the projected image of 1 when observed from a direction perpendicular to the plane 3 Two parallel lines tangent to 2 4 The maximum length of the parallel lines when sandwiched between 3 (longest axis diameter of primary particle) 5 The shortest length of the parallel lines when sandwiched between 3 (minor axis diameter of primary particle)
Claims
1. A pentasil-type zeolite having a water adsorption amount of 4.0 g / 100 g-zeolite or less under conditions of 25° C. and a relative humidity of 90%, and a major axis diameter of primary particles of 0.2 μm or more and 3.5 μm or less.
2. 2. The pentasil-type zeolite according to claim 1, characterized in that the aspect ratio of the primary particles is 1.0 or more and 2.5 or less.
3. SiO 2 / Al 2 O 3 3. The pentasil-type zeolite according to claim 1, wherein the molar ratio is 200 or more.
4. BET specific surface area is 300m 2 The pentasil-type zeolite according to any one of claims 1 to 3, characterized in that the zeolite has a molecular weight of 1 / g or more.
5. Na 2 The pentasil-type zeolite according to any one of claims 1 to 4, characterized in that the O content is 1.00 weight percent or less.
Citation Information
Patent Citations
Synthesizing method of zeolite
JP1993124811A
Production of pentasil zeolite
JP1997295812A
Pentasil structure type zeolitic material, its manufacture and its use
JP2007533580A
Molded articles made from hydrophobic zeolite-based materials and methods for manufacturing the same
JP2016535718A